Intrathecal buprenorphine versus fentanyl as adjuvant to 0.75% ropivacaine in lower limb surgeries - Arvinder Pal Singh; Ravinder Kaur; Ruchi Gupta; Anita Kumari (Wolters Kluwer Medknow Publications, 2016)
Background and Aims: This study aims to compare the anesthesia characteristics between buprenorphine and fentanyl when added as an adjuvant to intrathecal ropivaciane in an attempt to prolong the duration of spinal anesthesia. Material and Methods: The present prospective double-blind study was undertaken on ninety American Society of Anesthesiologist I and II patients between 18 and 60 years of age undergoing subarachnoid block for lower limb surgery. Group I (n = 30) patients were administered 3 ml of intrathecal solution (2.8 ml of 0.75% ropivacaine + 0.2 ml of isotonic sodium chloride), while Groups II and III patients (n = 30 each) received 2.8 ml 0.75% ropivacaine + 0.2 ml buprenorphine (60 μg) and 2.8 ml 0.75% ropivacaine + 0.2 ml fentanyl (10 μg), respectively. Following parameters were observed: Onset times and duration of sensory and motor block, time to first analgesic use, total dose of rescue analgesia, intra- and post-operative pain scores based on visual analog scale, sedation scores, hemodynamic parameters, and side effects if any. Data were analyzed by appropriate statistical tests and P < 0.05 were considered significant. Results: Time to onset of sensory and motor block in all the three groups was comparable. However, duration of sensory block was significantly prolonged in Groups II and III in comparison to Group I (P < 0.05) and it was the longest in Group II (P < 0.05). The duration of motor blockade was similar in all the three groups. The time to first analgesic dose was also significantly prolonged in Groups II and III as compared to Group I (P < 0.05) but was comparable between Groups II and III. Intra- and post-operative hemodynamic parameters, as well as side effects, were comparable. Conclusion: Addition of buprenorphine and fentanyl as adjuvants to intrathecal 0.75% ropivacaine prolongs postoperative pain relief without causing any increase in the duration of motor blockade but buprenorphine is better as compared to fentanyl in prolonging the duration of sensory block and achieving a better outcome in terms of pain relief.